Chemoselective Oxidation by Electronically Tuned Nitroxyl Radical Catalysts1. Issue 31 (21st June 2013) - Hamada, Shohei; Furuta, Takumi; Wada, Yoshiyuki; Kawabata, Takeo
<x xml:space="preserve">Abstract</x> Electronic tuning: Nitroxyl radical 1 is shown to be an efficient catalyst for the oxidation of secondary alcohols, and promotes oxidation through an oxoammonium species which is highly reactive because of the adjacent electron‐withdrawing ester groups. Chemoselective oxidation of benzylic alcohols in the presence of aliphatic alcohols is observed and is proposed to proceed by a rate‐determining hydride transfer.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>